Framed [compact disc, unabridged] : astonishing true stories of wrongful convictions - Grisham, John; McCloskey, Jim (Minister) (Random House Audio, 2024)
A fundamental principle of our legal system is a presumption of innocence, but once someone has been found guilty there is very little room to prove doubt. Framed shares ten true stories of men who were innocent but found guilty and forced to sacrifice friends, families, wives, and decades of their lives to prison while the guilty parties remained free. In each of the stories, John Grisham and Jim McCloskey recount the dramatic hard-fought battles for exoneration. They take a close look at what leads to wrongful convictions in the first place, and the racism, misconduct, flawed testimony, and the corrupt court system that can make them so hard to reverse.